Analisis Biaya Produksi Dan Harga Jual Dalam Menentukan Laba Bersih: Studi Kasus Pada Konveksi Indi’s Collection - Jasmadeti, Jasmadeti; Alpaidah, Alvi (Jurnal Aplikasi Bisnis Kesatuan, 2024)
Fashion is currently growing rapidly from year to year. Fashion in this world is very influential in its development of war, culture, politics, economic, social movements and many other supporters who take part in changing the existing fashion. Indi's Collection is a convection company which is the case study in this research. In determining the calculation of the cost of production, the Indi's Collection Convection still uses a very simple method and has not yet detailed all costs incurred in the production process. This study aims to find out the production cost calculations that have been carried out by the company in determining net profit on the Indi's Collection convection. selling price calculations that have been carried out by the company in determining Net Profit at Indi's Collection convection, calculating Production Costs using the Full Costing method, calculating Selling Prices using the Cost Pricing method – Plus, equal to find out whether there are differences in the calculation of Production Costs and Selling Prices based on company calculations using the full costing method and the cost-plus method in determining net profit on the Indi's Collection convection. The results of this study explain that the calculation of production costs carried out by Indi's Collection is still relatively simple without theoretical methods such as the cost accounting theory used in companies that produce a product. The selling price used is the market price of products of the same quality or can be calculated using the mark up method. The full costing method affects the cost of production produced in much more detail and is cheaper than the calculation obtained from the results of interviews with business owners. The use of Cost plus pricing in Indi's Collection can increase turnover and competitive prices by producing a much larger turnover at the previous selling price. At the selling price used, Indi's Collection is more relevant because the price used is the market price of similar products used in other convections. In the comparison of net income, Indi's Collection is considered to be inadequate in describing the cost of production and expenses contained in the income statement, so that the allocation of the translation in the financial statements is considered inappropriate. Keywords: Production Cost Analysis, Selling Price, Net Income